Health-related quality of life in Dutch adult survivors of childhood cancer: A nation-wide cohort study. (July 2021) - van Erp, L.M.E.; Maurice-Stam, H.; Kremer, L.C.M.; Tissing, W.J.E.; van der Pal, H.J.H.; de Vries, A.C.H.; van den Heuvel-Eibrink, M.M.; Versluys, B.A.B.; Loonen, J.J.; Bresters, D.; Louwerens, M.; van der Heiden-van der Loo, M.; et al.
Abstract: Aim: To investigate the health-related quality of life (HRQOL) of Dutch adult childhood cancer survivors (CCS) and to identify risk factors of impaired HRQOL. Methods: Adult CCS (age >18, diagnosed <18, ≥5 years since diagnosis) from the Dutch LATER registry completed the Medical Outcome Study Short Form 36 (SF-36) to measure HRQOL and provided sociodemographic characteristics. Age-adjusted mean SF-36 scale scores of CCS were compared to the Dutch general population for men and women separately using t-tests, with effect size d . Multivariate logistic regression models were built to identify sociodemographic and cancer-related risk factors for impaired physical and mental HRQOL. Results: Both male and female CCS (N = 2301, mean age = 35.4 years, 49.6% female) reported significantly ( p  ≤ .005) worse HRQOL than the general population on almost all scales of the SF-36 (−.11 ≤ d  ≤ −.56). Largest differences were found on vitality and general health perceptions. Significant risk factors ( p  ≤ .05) for impaired physical HRQOL were female sex, older age at diagnosis, not having a partner, low educational attainment, disease recurrence and exposure to radiotherapy, specifically to lower extremity radiation. Odds ratios (ORs) ranged from 1.6 to 3.7. Significant risk factors for impaired mental HRQOL were age 26–35 years, male sex, not having a partner and low educational attainment. ORs ranged from 1.3 to 2.0. Conclusion: Adult CCS had worse HRQOL than the general population. CCS most at risk were those with low educational attainment and without a partner. Adult CCS could benefit from routine surveillance of their HRQOL. Special attention for CCS' vitality and health perceptions and beliefs is warranted. Highlights: The first nationwide cohort study of health-related quality of life (HRQOL) in Dutch adult childhood cancer survivors (CCS) (N = 2301). Dutch adult CCS reports worse HRQOL than the general population. Cancer-related risk factors are associated with impaired physical, not mental HRQOL. Risk factors for impaired physical/mental HRQOL are low education and having no partner.